The role of personnel motivation in the risk management system of energy companies with employee stock ownership - Mnykh, O.; Мних, О.; Dikan, O.; Дікань, О.; Yukhnov, B.; Юхнов, Б; Kvasova, Lyudmyla; Квасова, Людмила Сергіївна; Shkvaryluk, L.; Шкварилюк, Л. (Published under licence by IOP Publishing Ltd, 2021)
Abstract.The impact of motivation of the personnel of joint-stock companies on increasing the efficiency of their economic activities and reducing management risks has been examined. The world experience in the development of property and management decentralization has been investigated. The current state of the functioning of companies with employee stock ownership has been analyzed, and main contradictions in the distribution of their income have been given. Specific recommendations have been given to resolve these contradictions in order to apply them by joint-stock companies of the energy sector of Ukraine in their economic activities. Досліджено вплив мотивації персоналу акціонерних товариств на підвищення ефективності їх господарської діяльності та зниження управлінських ризиків. Досліджено світовий досвід розвитку децентралізації власності та управління. Проаналізовано сучасний стан функціонування компаній з акціонерною власністю працівників та наведено основні протиріччя у розподілі їх доходів. Надано конкретні рекомендації щодо вирішення цих протиріч з метою їх застосування акціонерними товариствами енергетичного сектору України у своїй господарській діяльності.
Роль мотивації персоналу в системі ризик-менеджменту енергетичних компаній з акціонерною власністю працівників
Keywords: personnel of joint-stock companies; персонал акціонерних товариств; reduction of managerial risks; зниження управлінських ризиків; application of the energy sector of Ukraine; застосування енергетичного сектору України; contradictions in income distribution; протиріччя у розподілі доходів